Social Learning Theory and Youth Behaviour in Social Media Environments - Chiwendu, Atuanyaeme Faith (BIRCU, 2026)
The paper is on the analysis of social learning theory on social media life among Nigerian youth. Social media have fundamentally changed the way social interaction occurs among Nigerian youth by providing platforms for improving learning in a social context. This study analysis the positive and negative influence of the social media life on Nigerian youth, due to the fact that it has also exposed the youth to different varieties of social vices which has negatively questions the essence of social learning theory in character molding. Using an empirical review of existing literature and scholarly studies, the paper examines how social media exposure influences youth identity formation, attitudes, and social behaviour. Findings indicate that social media acts as a powerful agent of socialization that reinforces behavioural imitation through mechanisms such as likes, comments, and shares. While social media can promote creativity, social awareness, and knowledge sharing, it can also encourage harmful behaviours such as cyberbullying, risky online challenges, and unrealistic lifestyle expectations. The study concludes that social media literacy and responsible digital engagement are essential in guiding positive youth development in contemporary society. The paper recommends that the role models such as teachers, parents, pastors, uncles, aunties and society at large should provide a platform that will constantly sensitize the youth on a more effective way on the use of social media.